2005
DOI: 10.1038/sj.bjc.6602753
|View full text |Cite
|
Sign up to set email alerts
|

Do septins have a role in cancer?

Abstract: Septins are an evolutionarily conserved family of genes that encode a P loop-based GTP-binding domain flanked by a polybasic domain and (usually) a coiled-coil region. They have roles in cytokinesis, vesicle trafficking, polarity determination, and can form membrane diffusion barriers, as well as in microtubule and actin dynamics. Septins can form hetero-oligomeric complexes and possibly function as dynamic protein scaffolds. Recently, it has been shown that there are at least 13 human septin genes that exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 32 publications
2
62
0
3
Order By: Relevance
“…The MLL fusion partner we have identified, SEPT2, belongs to an evolutionarily conserved family of genes that encode a P loop-based GTP-binding domain flanked by a polybasic domain and (usually) a coiled-coil region (Hall and Russell, 2004;Russell and Hall, 2005). The SEPT2 protein possesses all the three domains and shares a very high homology with septins 1, 4 and 5 (Hall and Russell, 2004).…”
Section: Mll-sept2 Fusion Gene In Aml N Cerveira Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…The MLL fusion partner we have identified, SEPT2, belongs to an evolutionarily conserved family of genes that encode a P loop-based GTP-binding domain flanked by a polybasic domain and (usually) a coiled-coil region (Hall and Russell, 2004;Russell and Hall, 2005). The SEPT2 protein possesses all the three domains and shares a very high homology with septins 1, 4 and 5 (Hall and Russell, 2004).…”
Section: Mll-sept2 Fusion Gene In Aml N Cerveira Et Almentioning
confidence: 99%
“…The SEPT2 protein possesses all the three domains and shares a very high homology with septins 1, 4 and 5 (Hall and Russell, 2004). Recently, it has been shown that there are at least 13 human septin genes (Russell and Hall, 2005). Four of them (SEPT5, SEPT6, SEPT9 and SEPT11) have already been cloned as MLL fusion partners (Megonigal et al, 1998;Osaka et al, 1999;Taki et al, 1999a;Ono et al, 2002;Kojima et al, 2004), with the N-terminal moiety of MLL fused to almost the entire open-reading frame of the partner septin gene (Russell and Hall, 2005).…”
Section: Mll-sept2 Fusion Gene In Aml N Cerveira Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…Mammalian septins are evolutionary conserved proteins that form filaments associated with cytoskeleton organization, membrane dynamics, mitosis, cytokinesis, and cell cycle progression (9,10). Recently, accumulating data suggest that some septin family members also participate in the pathogenesis of neoplasia (11) and neurodegenerative diseases (12). We had shown that SEPT9_i1 interacts with HIF-1α, but not with HIF-2α, to prevent its RACK1-mediated ubiquitination and degradation (13) and that SEPT9_i1 protein activates HIF-1 transcriptional activity and increases tumor growth and angiogenesis in prostate cancer xenografts (8).…”
Section: Introductionmentioning
confidence: 99%
“…Septins are found in all eukaryotes except higher plants (20,52) and are involved in a variety of cellular processes including cytokinesis, vesicle trafficking, cytoskeleton organization, polarity, and formation of diffusion barriers (35,39,44,53,62). Perhaps, not surprisingly given their roles in such critical processes, septin defects have been associated with many human diseases (29).…”
mentioning
confidence: 99%